2009
DOI: 10.1007/s00125-008-1243-1
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of lifestyle changes in the Finnish Diabetes Prevention Study

Abstract: Aims/hypothesis Subclinical inflammation confers an increased risk of type 2 diabetes, cardiovascular disease, neurodegenerative disorders and other age-related chronic diseases. Physical activity and diet can attenuate systemic immune activation, but it is not known which individual components of a comprehensive lifestyle intervention are most effective in targeting subclinical inflammation.Methods We used data from the baseline examination and the 1 year follow-up of a subsample of 406 of 522 participants of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
111
1
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(123 citation statements)
references
References 53 publications
7
111
1
4
Order By: Relevance
“…In the DPS, we also found beneficial changes in inflammatory markers [10], and blood pressure [11]. These also suggest that a moderate relative increase in carbohydrates, e.g.…”
supporting
confidence: 72%
“…In the DPS, we also found beneficial changes in inflammatory markers [10], and blood pressure [11]. These also suggest that a moderate relative increase in carbohydrates, e.g.…”
supporting
confidence: 72%
“…In conclusion our results have shown that nutritional status is moderately associated with HRQoL and lower limb strength, which is also associated with HRQoL in patients with T2DM. Physical activity and diet are the cornerstones in the prevention and treatment of T2DM (6,(43)(44)(45); Our data suggest that in the future more emphasis could be placed on interventions to enhance a correct diet through early identification of the risk for malnutrition and stress the needed to improve lower body strength to reinforce better mobility in T2DM population.…”
Section: Discussionmentioning
confidence: 99%
“…In the Finnish Diabetes Prevention Study increased fibre intake was one of two independent factors predicting decreases in circulating levels of CRP and IL-6 [46]. A recent review of dietary intervention trials reported that in six out of seven trials, daily consumption of 3-8 g fibre per megajoule led to significant decrements in plasma CRP concentrations of 25-54% [47].…”
Section: Dietary Fibre and Other Food Componentsmentioning
confidence: 99%
“…the promotion of insulin resistance and lipolysis, whereas in skeletal muscle insulin action is augmented [70]. It seems difficult to reconcile this systemic pro-inflammatory effect of intense muscle work with the observed anti-inflammatory effect of regular exercise [46,71]. One probable explanation is that the acute pro-inflammatory bout following intense physical exercise is followed by the increase in systemic levels of the anti-inflammatory cytokine IL-10 [72].…”
Section: Muscle Workmentioning
confidence: 99%
See 1 more Smart Citation